Sikap Bahasa Mahasiswa Pendidikan Bahasa Mandarin UNESA di Era Digital - Cindy Rachma Aulia; Aulia Widiyaningrum; Khalimatus Sa'diyah; Maria Mintowati; Rokhishotul Amaliyah (Universitas Negeri Makassar, 2026)
Abstract. This study is motivated by the increasingly dynamic use of language in the digital era, particularly among Generation Z, who actively engage with digital media. In the context of globalization, Mandarin, as one of the major international languages, plays an important role not only in academic settings but also in providing career opportunities and cross-cultural communication. However, in practice, the use of Mandarin among university students is not always aligned with their language attitudes. This study aims to analyze the language attitudes of Mandarin Language Education students of the 2024 cohort at Universitas Negeri Surabaya toward Mandarin in the digital era and to identify the influence of digital media on its use. This research employs a descriptive quantitative approach supported by qualitative data. Data were collected through an online questionnaire using Google Forms, consisting of closed-ended questions with a Likert scale and open-ended questions. The sample consisted of approximately 70 respondents from classes B and C. The results show that 95.8% of respondents use Mandarin in academic contexts, while its use in daily communication remains limited, with the majority of respondents (54.2%) using it only occasionally. Furthermore, digital media has a significant influence, with around 70% of respondents stating that it affects their interest in using Mandarin. These findings indicate a gap between positive language attitudes and actual language use in everyday life. This study contributes to understanding the dynamics of students’ language attitudes in the digital era and provides insights for developing more communicative and contextual Mandarin language learning strategies. Keywords: language attitude, Mandarin, Generation Z, digital media, sociolinguistics